84.0k views
4 votes
Solve the system of equations 2x - y = 11 and x + 3y = -5

User Ndfred
by
4.9k points

2 Answers

4 votes

Answer:

(7, 3)

Explanation:

2x - y =11 2x-y =11

-2(x+3y)= (-5)-2 -2x-6y= 10

Then you will cross out the x, and add.

-7y =21 divide 7

y=-21/7 or y=3

Then you plug in the y where the y is and solve

2x-(3) = 11

2x = 14

x=7

User BruneauB
by
5.5k points
3 votes

Answer:

x = 4, y = -3

Explanation:

{2x - y = 11

{x + 3y = -5

You can use the substitution method by solving for x in the second equation:

x + 3y = -5

Subtract 3y from both sides:

x = -3y - 5

Now, substitute this value for x into the first equation:

2x - y = 11

2(-3y - 5) - y = 11

Distribute:

-6y - 10 - y = 11

Add 10 to both sides:

-6y - y = 21

Combine like terms:

-7y = 21

Divide both sides by -7:

y = -3

Next, substitute this value for x into the second equation:

x + 3y = -5

x + 3(-3) = -5

Multiply:

x - 9 = -5

Add 9 to both sides:

x = 4

User Boxed
by
6.0k points